LncRNA HCG18 upregulates TRAF4/TRAF5 to facilitate proliferation, migration and EMT of epithelial ovarian cancer by targeting miR-29a/b - Fan Zhang; Bai-Hua Luo; Qi-Hui Wu; Qing-Ling Li; Ke-Da Yang (BMC, 2022)
Abstract Background Although long noncoding RNA HLA complex group 18 (lncRNA HCG18) has been suggested to regulate cell growth in several tumours, the function of HCG18 in epithelial ovarian cancer (EOC) and its mechanism are still unclear. Methods shRNAs were applied to reduce HCG18 and related genes. For overexpression of miRNA, a miRNA mimic was transfected into cells. Quantitative real-time PCR (qRT-PCR) was used to detect levels of HCG18, miR-29a/b, and mRNAs. MTT, colony formation, wound healing and Transwell assays were used to evaluate cell proliferation, migration and invasion, respectively. A luciferase reporter assay was utilized to evaluate NF-κB activity and the binding of miRNAs with HCG18 or TRAF4/5. BALB nude mice injected with cells stably expressing shHCG18 or shNC were used for in vivo modelling. Subcutaneous tumour growth was monitored in nude mice, and immunohistochemistry (IHC) was used to determine expression of the proliferation marker Ki67. Results Abnormal expression of HCG18 and miR-29a/b was observed in EOC tissues. Knockdown of HCG18 using shRNA inhibited proliferation, migration, EMT and the proinflammatory pathway in EOC cells. miR-29a/b mimics and TRAF4/5 knockdown exhibited effects similar to HCG18 knockdown. Further experiments suggested that HCG18 directly targets miR-29a/b and upregulates TRAF4/5 expression, which are inhibited by targeting miR-29a/b. Moreover, overexpression of TRAF4/5 antagonized the inhibitory effect of HCG18 knockdown, suggesting that they are involved in HCG18-mediated oncogenic effects. Silencing HCG18 reduced tumour size and levels of Ki67 and TRAF4/5 while increasing miR-29a/b levels in vivo. Conclusions Taken together, our data revealed an oncogenic signalling pathway mediated by HCG18 in ovarian cell lines, which functions as a ceRNA of miR-29a/b and thus derepresses expression levels of TRAF4/5, facilitating NF-κB pathway-mediated promotion of EOC cell proliferation and migration.